Integrative Biology − the challenges of developing a collaborative research environment for heart and cancer modelling - Lloyd, S; Gavaghan, D; Simpson, A; Mascord, M; Seneurine, C; Williams, G; Pitt−Francis, J; Boyd, D; Mac, R; Sastry, L; Nagella, S; Weeks, K; et al. (2007)
The Integrative Biology project is building a Grid infrastructure which will enable biomedical scientists to develop accurate multi-scale computational models of the heart and of cancer tumours. This infrastructure will remove many of the constraints limiting research progress today by providing access to leading-edge supercomputing and data management resources and by improving facilities to support collaboration